High-Intensity Exercise Training Alters the Effect of N-Acetylcysteine on Exercise-Related Muscle Ionic Shifts in Men - Anders K. Lemminger; Matteo Fiorenza; Kasper Eibye; Jens Bangsbo; Morten Hostrup (Antioxidants, 2022)
This study investigated whether high-intensity exercise training alters the effect of N-acetylcysteine (a precursor of antioxidant glutathione) on exercise-related muscle ionic shifts. We assigned 20 recreationally-active men to 6 weeks of high-intensity exercise training, comprising three weekly sessions of 4–10 × 20-s all-out bouts interspersed by 2 min recovery (SET, n = 10), or habitual lifestyle maintenance (n = 10). Before and after SET, we measured ionic shifts across the working muscle, using leg arteriovenous balance technique, during one-legged knee-extensor exercise to exhaustion with and without N-acetylcysteine infusion. Furthermore, we sampled vastus lateralis muscle biopsies for analyses of metabolites, mitochondrial respiratory function, and proteins regulating ion transport and antioxidant defense. SET lowered exercise-related H+, K+, lactate−, and Na+ shifts and enhanced exercise performance by ≈45%. While N-acetylcysteine did not affect exercise-related ionic shifts before SET, it lowered H+, HCO3−, and Na+ shifts after SET. SET enhanced muscle mitochondrial respiratory capacity and augmented the abundance of Na+/K+-ATPase subunits (α1 and β1), ATP-sensitive K+ channel subunit (Kir6.2), and monocarboxylate transporter-1, as well as superoxide dismutase-2 and glutathione peroxidase-1. Collectively, these findings demonstrate that high-intensity exercise training not only induces multiple adaptations that enhance the ability to counter exercise-related ionic shifts but also potentiates the effect of N-acetylcysteine on ionic shifts during exercise.